Analisis Pengaruh Lingkungan Kerja dan Kompetensi Terhadap Kepuasan Dosen Tidak Tetap pada Universitas 17 Agustus 1945 Surabaya - Valentino Orlando Febrian; Bowo Santoso (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The satisfaction of non-permanent lecturers at the University of 17 August 1945 Surabaya due to the work environment and competence is the study of this research. With 57 non-permanent lecturers in the population, this research uses a quantitative and limited approach using saturated samples. By using data collection techniques through a Likert scale questionnaire, the data were analyzed using Partial Least Square (PLS) to measure the outer and inner models. The results of this study indicate that the Work Environment has a positive and significant influence on job satisfaction, while competence has a negative and insignificant influence on job satisfaction. This means that job satisfaction will be higher if an institution has a more conducive work environment, competence is one aspect of professionalism, but not all make someone feel more satisfied in working.